Respons Sosial terhadap Kebakaran di TPA Puuwatu melalui Penyaluran Bantuan Kebutuhan Pokok - Al, Rajab; Fajar Kurniawan; Lisnawati; Tawakal; Sultan Andilah; Marheni Fadilah Harun; Fitri Kurniawati; Noviani Munsir; Rania Fatrizza Pritami; Ira Nurmala; Efa Kelya Nasrun; Teti Susliyanti Hasiu; Hasmita; Alfilnah; Wisny Madaniansyah; Deden Dwiprasetya; Zulfikar (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
On February 14, 2025, a massive fire struck the Final Waste Disposal Site (TPA) in Puuwatu, Kendari City, destroying 52 houses owned by sanitation workers and causing material losses estimated at IDR 1.1 billion. This incident had a significant social and economic impact, particularly on low-income communities who rely on the informal waste management sector. In response to this emergency, lecturers and students from STIKES Pelita Ibu Kendari carried out a community service initiative. The main objectives were to provide targeted basic necessities and offer psychosocial support to affected victims. The activities were conducted through participatory and collaborative approaches, including coordination, needs assessment, fundraising, and direct distribution of aid such as food staples, decent clothing, and other essential supplies. Additionally, the team organized emotional support activities for children and the elderly. The presence of the service team proved effective in strengthening psychosocial resilience and enhancing solidarity among residents. This initiative is expected to serve as a model for community-based emergency response that can be replicated in other regions.